The transmission of US cyclical developments to the rest of the world - Stéphane Dées; Isabel Vansteenkiste (European Central Bank (ECB), 2007)
The US economy is often considered to play a pivotal role in global growth. Such a view has persisted despite the falling contribution of the US economy to global growth (from almost 30% in 1950 to around 20% at present). In this paper, we analyse the veracity of this conjecture and consider the implications of cyclical developments in the US economy on the rest of the world. Overall we find that while US economic developments would indeed affect the rest of the world, developments in most countries and regions remain primarily affected by idiosyncratic shocks as well as by global factors, which do not originate from a single country.
Keywords: E32; E37; F41; 330; business cycle; Factor models; Global VAR model; Markov-switching model; Konjunkturzusammenhang; USA; Welt